2018
DOI: 10.1177/1354068817753060
|View full text |Cite
|
Sign up to set email alerts
|

Breaking a habit: The impact of health on turnout and party choice

Abstract: Turnout and party choice are widely held to be habitual, but little attention has been paid to factors that disrupt the pattern. Good health is an important determinant of political behaviour and a key component in the quality of life. Based on the developmental theory of turnout, we hypothesize that declining health lowers voting propensity over the life course. We employ issue ownership theory to assume that declining health increases the likelihood of voting for leftist parties. Using the British Household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…In the case presented, people who reported feeling stressed were more likely to vote for the party that is on the right side of the political spectrum and that has a specific transportation project that differs from the other parties. This result contradicts other studies that show that people whose health is deteriorating or otherwise impaired tend to vote more to the left (Rapeli et al, 2020). That hypothesis is confirmed in our results for mental health, but not for stress.…”
Section: Concluding Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In the case presented, people who reported feeling stressed were more likely to vote for the party that is on the right side of the political spectrum and that has a specific transportation project that differs from the other parties. This result contradicts other studies that show that people whose health is deteriorating or otherwise impaired tend to vote more to the left (Rapeli et al, 2020). That hypothesis is confirmed in our results for mental health, but not for stress.…”
Section: Concluding Discussioncontrasting
confidence: 74%
“…Some studies have also shown the existence of a link between political ideology and health (Subramanian and Perkins 2010) and have argued that ideology mediates the relationship between health and vote choice (Rapeli et al, 2020). Some analyses thus show that healthy people are more to the right of the political spectrum while those with poorer health tend to be more to the left and vote accordingly.…”
Section: Stress and Vote Choicementioning
confidence: 99%
“…In general, if the expected payoffs are low, compared to the required investment, self-interest will not affect an individual's political behaviour. However, deteriorating health can be a factor that motivates people to act out of self-interest: the payoff for a favourable policy outcome is higher when a person needs support from the public healthcare sector to cope with personal health problems (Rapeli et al, 2019).…”
Section: Theoretical Approachesmentioning
confidence: 99%
“…Nevertheless, the negative effect is not restricted to seniors. Population-level survey studies have shown how poor physical or mental health depresses voting in Ireland (Denny and Doyle, 2007a), in the UK (Denny and Doyle, 2007b;Rapeli et al, 2019), in Europe in general (Mattila et al, 2013), in Canada (Couture and Breux, 2017), in the Nordic countries (Söderlund and Rapeli, 2015) and in the USA (Gollust and Rahn, 2015;Pacheco and Fletcher, 2015;Burden et al, 2017;Ojeda and Slaughter, 2019). The results somewhat vary depending on the country or type of election concerned, but generally the difference in turnout is about 10 percentage points between the opposite ends of the five-point SRH scale.…”
Section: Forms Of Participation and Healthmentioning
confidence: 99%
“…Our study contributes to the literature in two ways. First, although there is a growing body of research on the effect of health on political participation (e.g., Couture and Breux [2017]; Mattila et al [2013]; Ojeda and Pacheco [2017]; Rapeli et al [2018]), this is the first study to analyse the effect 3 of health on party identification. This is important since studies of the effect of health on behavioural indicators capture its effect as a consequence of party identification and not on the concept itself (Burden and Klofstad 2005), that is, psychological and not behavioural.…”
Section: Introductionmentioning
confidence: 99%